1997
DOI: 10.1038/hdy.1997.42
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis for different host use in Epilachna pustulosa, a herbivorous ladybird beetle

Abstract: The genetic basis for different host plant use was studied in a herbivorous ladybird beetle, Epilachna pustulosa, that exhibits interpoputational variation in host plant utilization. It usually depends on thistle, but one of the local forms occurs on both thistle and blue cohosh, which differ at the infraclass taxonomic level. In this local population, genetic association between the developmental performance on the two plants was neutral, suggesting genetic independence across the host plants. The form of rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…However, negative correlations were found in only a limited variety of species (Gould, 1979;Fry, 1990;Via, 1991). Instead of a negative genetic correlation, either positive or no genetic correlations were commonly reported in previous studies (Rausher, 1984b;Via, 1984;Hare & Kennedy, 1986;Futuyma & Philippi, 1987;James et al, 1988;Jaenike, 1989;Karowe, 1990;Fox, 1993;Lu et al, 1997;Ueno et al, 1997Ueno et al, , 1999Balabeni & Rahier, 2000).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, negative correlations were found in only a limited variety of species (Gould, 1979;Fry, 1990;Via, 1991). Instead of a negative genetic correlation, either positive or no genetic correlations were commonly reported in previous studies (Rausher, 1984b;Via, 1984;Hare & Kennedy, 1986;Futuyma & Philippi, 1987;James et al, 1988;Jaenike, 1989;Karowe, 1990;Fox, 1993;Lu et al, 1997;Ueno et al, 1997Ueno et al, , 1999Balabeni & Rahier, 2000).…”
Section: Introductionmentioning
confidence: 70%
“…*P < 0.05; **P < 0.01; ***P < 0.001. (Kurosawa, 1953;Ueno et al, 1997;Yamaga & Ogushi, 1999), the high growth performance on blue cohosh appears to be a consistent characteristic of Sapporo populations. The high affiliation of Sapporo populations to blue cohosh is also suggested by a greater preference for the host-plant in comparison with populations from other localities (Hoshikawa, 1984).…”
Section: Survivalmentioning
confidence: 95%
“…Hoshikawa (1984) conducted a laboratory preference test and also showed that females of E. pustulosa, collected from the suburbs of Sapporo, preferred blue cohosh over thistle. Ueno et al (1997) also showed that E. pustulosa larvae perform better on blue cohosh than on thistle in the laboratory. They found that larvae on blue cohosh had signi®cantly higher larval survival, shorter development times to adult emergence and larger body size in both sexes than those on thistle.…”
Section: Bottom-up Eects On Ospring Performancementioning
confidence: 89%
“…Such trade-offs should be linked to negative genetic correlations of larval fitness traits across hosts, favouring the evolution of hostspecialised genotypes that could theoretically lead to speciation (see Via, 1990;Jaenike, 1990). However, negative across-host genetic correlations of larval performance traits have rarely been found (e.g., recently Ueno et al, 1997;Keese, 1998;Lazarevic et al, 1998;discussed in, among others, Rausher, 1988discussed in, among others, Rausher, , 1992Jaenike, 1990;Via, 1990;Thompson, 1994;Joshi & Thompson, 1995;Fry, 1996). Recently, it has been proposed that negative genetic correlations may not be necessary for host specialisation to evolve, but that a significant statistical interaction of larval performance traits between insect genotypes and host plant could suffice (Fry, 1996).…”
Section: Introductionmentioning
confidence: 99%